PENGARUH EARNINGS PERSISTENCE, GROWTH OPPORTUNITY, DAN DEFAULT RISK TERHADAP EARNINGS RESPONSE COEFFICIENT PADA PERUSAHAAN PROPERTY DAN REAL ESTATE - Fitriani, Annisa; Sumiyati, Sumiyati; Julia, Julia (LPPM Universitas Bina Bangsa, 2025)
This study aims to empirically examine the effect of earnings persistence, growth opportunity, and default risk on earnings response coefficient in property and real estate companies listed on the IDX for the 2021-2023 period. This research uses a quantitative descriptive approach. The population of this study consists of 93 property and real estate companies listed on the IDX for the 2021-2023 period. Sample selection using purposive sampling method which resulted in a sample size of 31 property and real estate companies, so that a total of 93 processing data was obtained for a three-year period. Analysis using panel data regression. The results showed that earnings persistence has a positive and significant effect on ERC, while growth opportunity and default risk have no significant effect on ERC.